Regional integration in the 1990s. - ROSENTHAL, Gert (1993)
Examines the reawakened interest in intraregional cooperation in Latin America and the Caribbean. Concludes that (1) economic integration can enhance competitiveness in the international market; (2) recent intra-Latin American integration pacts abide by the spirit and letter of GATT while seeking to raise the level of competitiveness and promote market diversification; (3) as the globalisaton of the economy proceeds, tariff preferences as well as rules of origin and safeguards are taking on a different meaning from what they signified in a situation marked by high levels of tariff protection; (4) the diversity of existing regional integration movements makes it difficult to envision the configuration of a regionwide free trade area in the foreseeable future; (5) there is a limit to how many agreements there can be, since, under certain circumstances, different agreements could conflict with one another; (6) in situations where the countries engage in a considerable volume of reciprocal trade, have similar production structures and are geographic neighbours, there will be a strong tendency to complement a free trade area or a system of trade preferences with a common tariff in order to ward off distortions in resource allocation and to avoid encouraging contraband trade; (7) trade preferences can and should be complemented by other joint measures to resolve shared problems in a wide range of areas.